Reproducible and controlled peptide functionalization of polymeric nanoparticles - Chandrasiri, Indika; Liu, Yuxuan; Adjei-Sowah, Emmanuela; Xiao, Baixue; Benoit, Danielle S. W. (Frontiers in Biomaterials Science, 2022)
Polymeric nanoparticles containing multiple amines and carboxylates have been frequently used in drug delivery research. Reproducible and controlled conjugation among these multifunctional biomaterials is necessary to achieve efficient drug delivery platforms. However, having multiple functional groups increases the risk of unintended intramolecular/intermolecular reactions during conjugation. Herein, conjugation approaches and possible undesired reactions between multi- amine functional peptides, multi-carboxylate functional polymers, and anhydride-containing polymers [Poly(styrene-alt-maleic anhydride)-b-poly(styrene)] have been investigated under different conjugation strategies (carbodiimide chemistry, anhydride ring-opening via nucleophilic addition elimination). Muti-amine peptides led to extensive crosslinking between polymers regardless of the conjugation chemistry. Results indicate that conventional peptide quantification methods (i.e., o-phthalaldehyde assay, bicinchoninic acid assay) are unreliable. Gel permeation chromatography (GPC) provided more accurate qualitative and quantitative evidence for intermolecular crosslinking. Crosslinking densities were correlated with higher feed ratios of multifunctional peptides and carbodiimide coupling reagents. Selectively protected peptides (Lys-Alloc) exhibited no crosslinking and yielded peptide-polymer conjugates with controlled dispersity and molecular weight. Furthermore, anhydride ring-opening (ARO) nucleophilic addition elimination was successfully introduced as a facile yet robust peptide conjugation approach for cyclic anhydride-containing polymers.